Context Clues in Reading Text for Improving EFL Students’ Reading Skills - Norhayati; Catharina Elmayantie (English Language Education Study Program of STKIP PGRI Banjarmasin, 2022)
This research was purposed to describe the use of context clues in order to help students in improving their reading skills. There were still some difficulties in reading skill experienced by the students. The students at higher education have difficulties in reading comprehension because they have no motivation in reading habit; they read a little or nothing. Other students’ difficulties in reading comprehension were the low reading skill. However, it is known that reading and vocabulary are related to each others, so that the use of context clues is related to vocabulary. But it is also known that context clue also used in the sentence structures and the position of the main idea of the text. It can be concluded that the use of context clue can help students, either in secondary school or in higher education, to develop their practicing reading skill.